Potential connection between positive frustration in family leisure time and the promotion of adolescent autonomy - Rivas, Sonia; Albertos, Aranzazu (Frontiers in Psychology, 2023)
Family relationships during leisure time in adolescence have the potential to promote positive development, particularly in terms of autonomy. However, the scientific literature that links specifically positive family leisure to the development of adolescent autonomy is scarce, and lower when analyzing the role of frustration in leisure time. Grounded in Self-Determination Theory (SDT) this article examines the potential relationship between positive frustration in family leisure time and the promotion of adolescent autonomy. For that purpose, the manuscript addresses four objectives to be discussed consecutively: (1) to delimit the concept of adolescent autonomy and point out the difficulty of parental support; (2) to explore positive frustration, a concept aligned with Csikszentmihalyi’s theory of flow, as a construct that can promote socio-emotional development in adolescence; (3) to describe the components of family leisure; and (4) to understand how the experience of optimal frustration may be linked to the development of adolescent autonomy during family leisure time. From this central question, several additional inquiries emerge: the interplay of frustration and failure in adolescence, the importance of parents and adolescents spending quality time together, the enjoyment in structured family leisure time, the autonomy-supportive parenting in leisure time activities in relation to daily activities, the need to strengthen adolescent bonds developed in infancy, and the complexity of paternal and maternal autonomy granting.